QUANTITATIVE ASSESSMENT OF THE VALUE OF HUMAN LIFE IN RUSSIA AND IN THE WORLD - А. N. Zubets; А. V. Novikov (Финансы: теория и практика)
The authors of the article present modern approaches to the assessment of the value of human life abroad and in contemporary Russia, which can be used to determine the fair amount of compensation payments to victims in emergency situations of various natures. To this end, a wide range of initial data was used: the results of Russian and international sociological surveys, statistics of Rosstat, the World Bank, and other international databases. The analysis of the legislation carried out by the authors showed that the value of human life in Russia fixed in the normative acts is from 0.5 to 9.2 million roubles. The authors obtained estimates of material losses for the national economy due to the premature death of the average person as a result of emergency situations and for the individual household — they amount to 31.7 and 7.9–10.5 million roubles respectively (in 2017 prices). The authors also provided estimates of the value of the life of the average person in Russia, obtained on the basis of sociological surveys conducted in 2017. The average value of human life in Russia, obtained by methods of sociology, is 5.2 million roubles; the median value is 1.4 million roubles. The article presents the author’s method of assessing the value of human life, taking into account the material and moral damage caused to the family of the deceased, built on the balance of average life expectancy, per capita final consumption, and satisfaction of the population of different countries with their lives. As an equivalent of people’s satisfaction with their lives, the authors also used data on the level of domestic violence in society and the balance of migration flows, both at the national and regional levels. Within the framework of this method, the value of the life of the average person is the average increase in the level of individual consumption, necessary to restore a normal level of satisfaction with their lives in conditions of increased mortality and reduction of the average life expectancy. The article presents also the author’s calculations performed by this method for different groups of countries. It is shown that the total value of human life in the world as a whole is 4.6–4.7 million uS dollars in 2011 prices. In the group of countries with per capita consumption of more than 10 thousand uS dollars the value of human life reaches 18.5 million dollars per year. In the group of countries with incomes below this mark, the value of human life reaches 0.5–1.9 million dollars. According to the authors, in Russia, the “value” of human life should be 51–61 million roubles in the prices of 2017 (about 1 million uS dollars depending on the official exchange rate). The results of the study of the quantitative assessment of the value of human life in Russia are correlated with the conclusions about the social need for just compensation of the damage suffered by the families of the victims of natural, man-made and other emergencies.